Efektivitas E-Study Tingkat Sekolah Menengah Kejuruan Kota Padang - Renny Permata Saputri; Yuliawati Yunus; Monica Fransisca (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
The research was motivated by making efforts to prevent covid-19 in the learning process. Learning is online and offline, carried out to prevent the transmission of Covid-19 and time-saving learning is needed so that students can take advantage of the remaining learning time for active and creative independent learning activities. The purpose of this study was to determine the effectiveness of using blended learning media as a learning support media, in this case in the form of e-study. The population of this research is SMK students throughout the city of Padang with a sample of SMKN 2, 5, and 8 Padang as many as 75 students. Based on the calculation results, the effectiveness level is classified as effective with an average percentage of 79.09%. So it can be concluded that the use of blended learning as a media to support learning is categorized as an effective media.